Eocene mammals from volcaniclastic deposits of the Somun Cura Plateau: biostratigraphic implications for north Patagonia Paleogene - Kramarz, Alejandro Gustavo (2022)
The Paleogene terrestrial faunal succession and its associated bearing volcaniclastic deposits has been exhaustively studied in central Patagonia, but there is still no acceptable litho-bio-chronostratigraphic ordering for the extra-Andean North Patagonia. The only references on Paleogene mammals bearing deposits north to Chubut River are imprecise and contradictory. West to Ingeniero Jacobacci (Río Negro Province, Argentina), the paleontologist and archaeologist Rodolfo Casamiquela reported a fossiliferous succession with Casamayoran or Mustersan (Eocene) and Deseadan (Oligocene) mammals from rocks currently mapped as the Las Chacras Formation. This unit includes acid to intermediate tuffs, ignimbrites, paleosols, conglomerates, and basalts originated in a perivolcanic fluvial system, under a seasonal subhumid-humid climate according to predominant pedogenic features. As a result of our fieldworks and fossil collection in the area of Ingeniero Jacobacci, and the revision of the materials collected by Casamiquela in the forties and fifties (with well-known stratigraphic origin), we identified a single mammal association from the lower section of the Las Chacras Formation (here named the Lower Las Chacras fauna) composed by: Plesiofelis schlosseri Roth, 1903 (Sparassodonta), Trigonostylops Ameghino, 1897, Astraponotus Ameghino, 1901 (Astrapotheria), Propyrotherium Ameghino, 1901 (Pyrotheria), Pseudhyrax eutrachytheroides Ameghino, 1901, Eohegetotherium priscum Ameghino, 1901, Puelia sigma (Ameghino, 1901), Periphragnis Roth, 1899 (Notoungulata), Isutaetus depictus Ameghino, 1902 (Cingulata), and a new member of Adianthidae (Litopterna) and probably of Pichipilidae (Paucituberculata). This assemblage is closer to that derived from the Rosado Member of the Sarmiento Formation at Gran Barranca, central Patagonia (type locality of the Mustersan Land Mammal Age) dated in ca. 38 Ma (late middle Eocene). A pyroclastic flow associated to the bearing deposits of Ingeniero Jacobacci was dated (K-Ar) in 39.2±2 Ma, value compatible with the Mustersan age here inferred for the Lower Las Chacras fauna. The alleged occurrence of Deseadan mammals in these levels was based on remains of an isotemnid notoungulate incorrectly identified as a leontinid. The presence of the Tinguirirican (early Oligocene) notoungulate Eohegetotherium priscum, with more apomorphic dental traits than in its Eocene allies, and of an astrapotheriid more derived than Astraponotus suggests that some advanced faunal elements would have been established in North Patagonia earlier than in central Patagonia.